The Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Pajak UMKM Berdasarkan Peraturan Pemerintah Tentang Harmonisasi Perpajakan (Studi Kasus Di Kantor Pelayanan Pajak Pratama Kupang) - Elsi Siyanti Bara, I Komang Arthanana, Sarlin P. Nawa (JURNAL RISET AKUNTANSI JAMBI, 2024)
The aim of this research is to determine the factors that influence tax revenues based on government regulations regarding tax harmonization with a case studi at the Kupang Pratama Tax Service Office. The data analysis technique used in this this research is quantitative by distributing questionnaires directly to MSMEs registered with KPP Pratama Kupang. The sample used in this research was 100 MSMEs in Kupang City. The results of this research show that partially and simultaneously taxpayer compliance, tax rates, tax socialization, and the number of tax objects have an influence on tax revenue